PENGARUH TEPUNG LIMBAH TEGEL KERAMIK SEBAGAI FILLER TERHADAP PERMEABILITAS ADUKAN - V. Lilik Hariyanto (Universitas Negeri Yogyakarta, 2005)
ABSTRACTThis research aimed to investigate the permeability of mortar mixed withceramic tile powder, in order to find alternative filler material that can slow thepermeability speed of mortar.This experimental research used 120 samples in four categories of fillercomposition (0%, 35 %,37.5 % and 40 %). Mortar with composition of 1 cement: 4 sand : 0 ceramic tile powder (by weight) was used as control variable.Descriptive and statistical methods were used to analyse the results of thisresearch. The statistical analysis includes the value of mean (M) and standarddeviation (SO).From the results, it can be concluded that there were significant differencesregarding the value of permeability among the composition variations. Themaximum permeability could be reached by the mortar with composition of 1cement : 4 sand : 35 % ceramic tile powder and followed by the mortar withcomposition of 1 cement: 4 sand: 37.5 % ceramic tile powder and 1 cement: 4sand: 40% ceramic tile powder.Keyword: mortar filler, ceramic file powder, permeability